Analisis Perubahan Garis Pantai dengan Menggunakan Metode One-Line Model (Studi Kasus: Pantai Kecamatan Kuta, Bali) - Naila Makfiya; IGB Siladharma; I Wayan Gede Astawa Karang (Journal of Marine and Aquatic Sciences, 2020)
Construction along the coastline has impacts and threats to coastal areas. Incompatibility and deficiency in building construction along the coast can be detected by observing shoreline changes that happen before and after construction. Along with technology advances and science, coastline change can be detected by using numerical modeling. Beach in Kuta District in the Bali Province is a tourist destination that has a coastal erosion problem. Analysis of shoreline changes at the study location is estimated by using numerical simulations (one-line model) to find out the coastline changes that happen on Kuta District for 25 years after the construction of beach protector and sand nourishment. The results of numerical modeling shoreline changes in all study locations over 25 years show an erosion and accretion with the amount of erosion change rates ranging from 1 to 2 meters per year. The analysis coastline change in Kuta District shows that the changes are classified as moderate to large, on the beaches in the north of Kuta Village such as on the beach of Legian Village and beach of Seminyak Village which did not have protection or beach protector such as the German Beach and the Kuta Beach with breakwater, groyne, revetments or handling erosion with sand nourishment.